Hyperprogressive disease induced by PD-1 inhibitor monotherapy in lung adenocarcinoma with HER2 exon 20 insertion: report of two cases and review of literature - Guangjian Yang; Linyan Tian; Yan Wang (Discover Oncology)
Abstract Monotherapy with anti-programmed cell death protein 1 (PD-1) monoclonal antibody has been approved for the treatment of advanced non-small cell lung cancer with positive programmed cell death-ligand 1 (PD-L1) expression and oncogene wild type, which revealed survival benefit compared with chemotherapy. Nevertheless, certain patients develop rapid progression on anti-PD-1 inhibitor monotherapy. This novel pattern is called hyperprogressive disease (HPD), and the underlying mechanism and molecular characteristics still leaves not clear. Here, we reported two heavily pretreated advanced lung adenocarcinoma cases with HER2 exon 20 insertion who presented HPD after two cycles of anti-PD-1 inhibitor sintilimab monotherapy, and they both carried co-alterations in the PI3K/AKT/mTOR and cell cycle signaling pathway. We speculated that HER2 exon 20 insertion might be viewed as a potential biomarker to avoid single-agent immunotherapy in certain patients with driver mutations, or timely guide proper treatment strategies.